THE IMPACT OF TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE (TPACK) ON LEARNING OUTCOMES: A BIBLIOMETRIC REVIEW - Simangunsong, Marta Florentina; Waspada, Ikaputera; -, Rasto; Muhammad, Ilham (UHN IGB Sugriwa Denpasar, 2023)
This study aims to analyze the research landscape regarding Technological Pedagogical Content Knowledge (TPACK) which is related to learning outcomes, using the bibliometric analysis method. The data used comes from the Scopus database. After going through the four stages of the process (identification, screening, eligibility, and inclusion), 41 relevant data were obtained. The results showed that the most publications related to TPACK and learning outcomes occurred in 2022 with a total of 6 publications. Meanwhile, the most cited publication occurred in 2017 with 267 citations. The United States has had a major influence on TPACK research and study outcomes. The research focus is divided into three main parts, namely 1) engineering and curriculum; 2) teaching and student; and 3) technology integration. Several new themes in this field include self-regulation, children learning, self-assessment, teaching strategies, learning activities and educational computing. However, the TPACK keywords which were the most dominant in the three research focuses were not directly connected with the three new theme keywords, namely self-regulation, children learning, and teaching strategies. By understanding the trends and research focus related to TPACK and learning outcomes, researchers and education practitioners can obtain useful guidance for developing innovative and effective teaching strategies, as well as designing curricula that match students' learning needs. Keywords: bibliometric, learning outcomes, TPACK